The protection of public actors’ right to privacy in the context of the Hungarian judicial practice - Halász, Csenge (Publicationes Universitatis Miskolcinensis, Sectio Juridica et Politica, 2022)
There are a number of issues of legal interpretation related to the right to privacy of public actors. In the present study, after a dogmatic and taxonomic review, we examine the trends in Hungarian judicial practice and the latest challenges to the right to privacy of public actors, from which we seek to draw forward-looking conclusions.